Writing Henan Opera Guidebook for Teaching Students at Zhengzhou University, Henan Province, the People’s Republic of China - Renli, Li; Yodwised , Chutasiri; Booranakeithsakula, Puriwat (Journal of Roi Kaensarn Academi, 2024)
The purpose of this study are: 1) To study Henan opera from experts. 2) To writing Henan opera Guidebook. 3) To teach Henan opera for students Zhengzhou university. 4) To Evaluate the effectiveness of the teaching. This study adopts qualitative and quantitative research methods. In the qualitative research, it’s interviewed experts and made specific tracks suitable for sophomores according to the interviews of experts, with the aim of improving students’ interest in learning Henan Opera and their singing ability, and observing students’ learning dynamics. In the quantitative research, through the evaluation of the Teaching Guide Book of Henan Henan Opera by the International Olympic Committee, 19 sophomores were selected from 38 students in Zhengzhou University to carry out experiments. Combined with the Teaching Guide Book of Henan Henan Henan Opera, the test scores were collected and compared through formative tests (twice) and summative tests to test the learning effect of students using the Teaching Guide Book of Henan Henan Henan Opera. The results show that the teaching guide book of Henan Henan opera covers the basic knowledge, singing, performance skills and historical inheritance of Henan opera. Among them, the teaching guide for college students not only fully considers students’ interests and learning characteristics in content, but also broadens the traditional teaching methods and introduces modern educational means such as multimedia teaching and team cooperation teaching, which makes the teaching guide more practical and operational. The results of three tests show that: Henan Henan opera teaching guide book has a good guiding role in improving the ability of Henan students to learn Henan opera, and it also proves that Henan students are more and more enthusiastic about learning Henan opera. This guide book of Henan Opera is successful and can provide some reference experience for other universities.